Expression of recombinant bovine prethrombin-2 in E. coli and optimized conditions for its production in liquid culture - CHEN Jian-liang; GUAN Yi-xin; CUI Zhi-fang; YAO Shan-jing (浙江大学学报. 农业与生命科学版)
Vector with gene of recombinant bovine prethrombin-2 (pThr-2) was successfully cloned into E. coli BL21 (DE3) cells. After the recombinant bacterium cells were induced by IPTG and further culture, pThr-2 inclusion bodies were obtained. The fermentation conditions for the pThr-2 production were optimized. The inclusion bodies of the pThr-2 produced in the E. coli culture amounted to 110 mg/L, accounting for 21.7% of the total cell proteins.